THE INFLUENCE OF ARTIFICIAL INTELLIGENCE ON CRIMINAL LIABILITY - Maxim DOBRINOIU (Challenges of the Knowledge Society)
The nowadays deployment of Artificial Intelligence (AI) and its expected relatively rapid integration into various instances of the socio-economic or governmental life (e.g. household, health, industry, trade and so on) represent a great development opportunity for every nation, as well as a key element for the evolution of the mankind. The elements of AI have already started to take over certain human-type workouts or tasks, while it will take not so long until they will almost completely replace individuals in performing their jobs, and thus evolve from the status of simple tools to the status of “electronic persons” or even subjects of law. During their interaction with the human-dominated world, the AI-driven entities may either be in compliance or a conflict relationship with the law and the society protected by the law, especially when a loss, a damage or a casualty occurs. The article aims at studying the electronic persons’ behavior and pointing out whether would be possible or not to further treat the elements of AI as liable against the law, in general, and criminal law, in particular.